E.E. Cummings' modernism and the classics : each imperishable stanza - Rosenblitt, J. Alison (Classical presences, 2016)
This volume is a major, ground-breaking study of the modernist E.E. Cummings' engagement with the classics. It explores the significance of Cummings' Harvard training as a Classicist to his development as a poet and to his published work, and also contains an edition of new, previously unpublished material by Cummings himself